Endocrine-Resistant Breast Cancer: Mechanisms and Treatment - Hartkopf, Andreas D. (Breast Care (Basel), 2020)
BACKGROUND: Endocrine treatment is one of the most effective therapies for estrogen receptor-positive breast cancer. However, most tumors will develop resistance to endocrine therapy as the cancer progresses. This review focuses on the mechanisms and markers of endocrine-resistant breast cancer. In addition, current and future strategies to overcome endocrine resistance are discussed. SUMMARY: Several molecular mechanisms of endocrine resistance have been identified, including alterations in the ESR1 gene or in the PIK3CA/mTOR pathway. Meanwhile, CDK4/6, mTOR, and PI3K inhibition have shown to improve the efficacy of endocrine treatment and new promising approaches are being developed. KEY MESSAGE: Overcoming primary or acquired resistance to endocrine treatment remains a major challenge. Since the molecular mechanisms of endocrine resistance are manifold, optimal combination and sequencing strategies will have to be developed in the future.